Comparative Analysis of Fatal Construction Accident Types Revealing Safety Performance in the Services Sector - Anindya Monika Putri; A. Ferina Herbourina Bonita; Vina Levia Budiman; Andi Rista Irawati Tanrasula; Erniati Bachtiar (Structures, Infrastructure, Planning, Implementation, and Legislation, 2025)
Occupational safety remains a critical challenge in the Indonesian construction sector, contributing to over one-third of all national work-related fatalities. This study performs a rigorous quantitative analysis using a census of 102 official fatal accident records from BPJS Ketenagakerjaan and the Ministry of PUPR (2018–2023).  The findings confirm that Falls from Height are the dominant cause of fatalities (41.2%), followed by material strikes. Statistical modeling (Logistic Regression) identified that short work tenure (< 5 years, OR ≈ 2.5) and safety harness non-compliance (OR ≈ 3.0) are the strongest predictors of this high-risk accident type.  The study indicates a systemic failure in enforcing OHS protocols, particularly concerning work-at-height hazards and Personal Protective Equipment (PPE) compliance. The novelty lies in the systematic use of national fatality census data coupled with risk modeling to empirically validate specific behavioral and demographic factors contributing to the most prevalent fatality type in Indonesia.  This work provides a strong empirical basis for developing evidence-based OHS policies, emphasizing the urgent need for stringent regulatory enforcement and targeted safety training for vulnerable worker groups.